PATTERN OF PSYCHIATRIC REFERRALS IN A TERTIARY CARE PUBLIC SECTOR HOSPITAL OF KARACHI - Haider, Anum; Saima Qureshi,; Kheenpal das,; Muhammad Ilyas Jat ,; Muhammad Tariq Arain, (Journal of Postgraduate Medical Institute, 2022)
Objective: To observe the frequency and pattern of Psychiatric referrals by Emergency and In-patient Departments (IPD) of tertiary care public sector hospital of Karachi. Methodology: A comparative cross-sectional study was conducted in the referred cases of Emergency (ER) and In-patient Department (IPD) for Psychiatric consultation from December 2019 to May 2020. The available medical records and International Classification of Diseases (ICD-10) diagnostic criteria were used for assessment and the record register was maintained on regular basis for data collection. The Data was analyzed to compare the findings in both ER and IPD. Results: There was a total of 281 referrals recorded in the register during six months. Among those112 (39.9%) were made from ER while 169 (60.1%) were from IPD. Most of them were young (33.4±13.5 years) and were almost equally distributed in both genders [Male=141 (50.2%) and Female=140 (49.8%)]. Altered or disorganized behavior, 88 (31.3%) followed by unexplained somatic complaints, 36 (12.8%,) and past psychiatric history, 25 (8.9%) were the most frequent reason for a referral from IPD. Suicide and deliberate self-harm were more common in ER (12, 4.3%) than that in IPD (6, 2.1%). Conclusion: Overall the frequency of Psychiatric referrals was low in comparison to the patient population and most of those were from the inpatient department than the ER.